Possibilities for the digital literacy of the older people in times of social distancing - Rodrigues, Kamila Rios da Hora; Onuki, Lucas Akio Senaga; Assunção, Danillo Magalhães Xavier; Gazola Junior, Sidnei; Pimentel, Maria da Graça Campos (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2020)
The world community recognizes that the pandemic caused by the SARS-Cov-2 virus has consequences for the mental health of individuals and demands actions from all sectors of society to minimize the impacts. For older people the consequences are even greater. In addition to being in the risk group, the quality of life of these people had impaired, since they had their routine changed, they are away from their friends/family and with suspended physical/ personal/cultural activities. This paper reports actions taken to ensure the continuity of digital literacy classes offered to the older people by the University of São Paulo. After a preliminary investigation with the older people of these classes, it was possible to observe a lack of them to this activity that used to represent new learning - towards your autonomy - and social interaction with colleagues, monitors and teachers. The team of teachers and monitors then joined forces to deliver classes and activities remotely. Several challenges were overcome and others are yet to be resolved. This paper brings the reports and results - so far - of this initiative.